Implementasi Model Project Based Learning Pada Buku Siswa Sekolah Dasar - Puiha Puji Mayada; Yunika Afryaningsih; Muhammad Aqmal Nurcahyo (Universitas PGRI Palembang, 2023)
This research is motivated by the policy that elementary school textbooks used in learning should incorporate the project-based learning (PjBL) model, thus requiring further analysis on the level of PjBL implementation in elementary school textbooks. The analysis was conducted on the fifth-grade elementary school textbooks. A descriptive qualitative approach was used in the research, supported by documentation data and structured questionnaires given to teachers. The results of the research show that there is content related to the PjBL model in the fifth-grade elementary school textbooks and it has been implemented to a